Determinan Loyalitas Konsumen Mie Gacoan Di Yogyakarta - Vetyandani Safrina Putri; Murwanto Sigit (Universitas 45 Surabaya, 2023)
This research was conducted to determine the factors that influence consumer loyalty gacoan noodles in Yogyakarta. The population of this research is all gacoan noodle customers in Yogyakarta. The number of samples in this study were 150 samples with the convenient sampling method, where the samples used represented the population. Testing the hypothesis in this study used Structural Equation Modeling (SEM) analysis with the help of AMOS 24 software. The results of this study indicate that there is a positive and significant influence on the variables of service quality, perceived price fairness, customer satisfaction, and customer loyalty.